Are there multiple bubbles in the ethanol–gasoline price ratio of Brazil?. (December 2015) - El Montasser, Ghassen; Gupta, Rangan; Martins, Andre Luis; Wanke, Peter
Abstract: This paper tests for the existence of bubbles in the ethanol–gasoline price ratio in Brazil from 2000 to 2012 using right-tailed ADF tests. Results suggest the existence of two bubbles: one which has already burst (during the re-election of President Lula); and one which has been ongoing since 2010, thus corroborating empirical and anecdotal evidence in the Brazilian sugarcane industry. Freezing gasoline prices not only depressed ethanol prices but also depressed investments in new sugarcane crops and distillation plants.